Potential benefits of vitamin A and its derivatives in glaucoma - Xinyue Zhang; Honghao Yang; Xiaoyu Zhou; Jiahao Xu; Jiawei Chen; Li Liao; Ping Wu; Xuanchu Duan (European Journal of Medical Research)
Abstract Vitamin A (VA), which plays a vital role in maintaining normal eye functions, has shown potential benefits in glaucoma based on accumulating evidence. The purpose of this review is to comprehensively summarize the possible role of VA and VA derivatives in the prevention and treatment of glaucoma, explore their mechanisms of action, suggest future research directions, and provide references for relevant researchers. Regarding the correlation between VA intake and glaucoma, researchers in different regions have conducted a series of studies, but most of them are cross-sectional studies. The results of different studies vary greatly and there are conflicting results, but the results of several systematic reviews and meta-analysis suggest that dietary VA intake can help reduce the risk of glaucoma. If increasing total dietary VA intake is successful as an effective prevention strategy, this would be a promising approach for primary prevention of glaucoma. Further, we summarized a large number of mechanism studies which have demonstrated the mechanisms of how VA might play a role in the prevention and treatment of glaucoma by inhibiting the oxidative stress process of trabecular meshwork and optic nerve tissue, reversing the effect of TGF-β2 on human trabecular meshwork cells and increasing intracranial pressure. Additionally, studies have also shown that VA and its derivatives could also play a role in preventing postoperative scarring and damage of the ocular surface due to the use of antiglaucoma drugs through a variety of mechanisms.